INTERNAL AND EXTERNAL FACTORS AFFECTING CUSTOMER LOYALTY OF BANK SUMUT - Mahyuni Miraza; Harmen Nasution; Iskandarini (CV. Radja Publika, 2024)
The number of Bank SUMUT clients had fluctuations throughout the years. In 2018, there were 2,813 customers, which decreased to 2,247 in 2019. In 2020, the number further declined to 1,031, but showed a little increase to 1,291 in 2021. However, in 2022, the number of Bank SUMUT customers significantly dropped to 828. Observing the data, it is evident that there was a decline in the customer base of Bank SUMUT between 2018 and 2020, followed by an increase from 2020 to 2021. However, there was another decrease in the number of Bank Sumatra customers between 2021 and 2022. This fluctuation can be attributed to various factors, both internal and external. The objective of this study is to identify and examine the intrinsic and extrinsic elements that impact customer loyalty at North Sumatra Bank. The population for this study consists of consumers who have accounts with Bank SUMUT Medan Coordinating Branch Office throughout the period of 2021-2022. The total number of samples to be collected in this study, when rounded up, is 100. The used sampling approach is simple random sampling. The data analysis technique employs Structural Equation Modeling-Partial Least Squares (SEM-PLS). The study findings indicate that Internal Factors have a favourable and substantial impact on Customer Loyalty at Bank SUMUT. Exogenous influences have a favourable and substantial impact on the loyalty of Bank SUMUT customers.